“Would they not wish the feast might ever last?”: Strong Spice, Oral History and the Genesis of Globe to Globe - Quarmby, Kevin (Multicultural Shakespeare: Translation, Appropriation and Performance, 2014)
The 2012 Globe to Globe Festival proved a great success. Actors, directors, musicians, dancers, designers and technicians travelled from all over the world to perform on the Globe stage. Visitors to London’s Cultural Olympiad enjoyed six jam-packed weeks of Shakespeare, presented in an array of international languages. The Globe’s Artistic Director, Dominic Dromgoole, and his Festival Director, Tom Bird, had achieved what seemed, to many, the impossible. Nonetheless, filmed interviews with Dromgoole and Bird, conducted during the festival by the American documentary-maker Steve Rowland, offer tantalizing insights into the genesis of the festival venture. These candid interviews confirm the sometimes farcical, often exhausting, but invariably serendipitous truth behind the Globe to Globe Festival’s short, intense history. Although the Globe was “flying completely blind,” it still succeeded in hosting a glorious feast of Shakespearean delights, seasoned with the strong spice of multiculturality.